Universities. policies for science and higher education - Rodrigues, M. L.; Guerreiro, M. D. (Disentangled vision on higher education: Preparing the generation next, 2023)
Envisaging universities of the future requires taking into account the speed of change and faster transformational processes that characterise contemporary societies. To succeed in such a scenario, individuals must have the ability to continue learning throughout life. Lifelong learning is closely dependent on a general, broad, non-specialised initial training. Higher education and science institutions face the ongoing challenge of the pedagogical and curricular organisation of their courses and training programmes, responding both to the need for generalist vs. specialised skills, and the need for lifelong training. At the root of such dynamics are the principles of autonomy and freedom to teach and undertake research, followed by a virtuous balance of openness to society and the incorporation of certain issues on the scientific agenda (social, economic, technological, public health, etc.). Taking the multilevel impact of the current COVID pandemic as a starting point, this chapter reflects on universities of the future and their role within the 2030 Sustainable Development Goals framework.